The Effect of New Technology in Payment Services on Banks' Intermediation - Kjersti-Gro Lindquist (Norges Bank, 2002)
In many countries, payment services in banking have shifted from paper-based giro and cheque payments to electronic giro and debit card payments. This paper analyses the effect of this change in payment technology within a multiple-output framework using Norwegian bank-level panel data. The dual approach with four variable inputs is applied, and the general model includes random coefficients to capture heterogeneity in production technology across banks. The results show that the move towards electronic payment services has decreased average costs and increased the economies of scale in bank intermediation. An output composition effect can explain that decreasing economies of scale is often found in analyses of banks.
hdl:11250/2498664
Keywords: C33; G21; O33; 330; banking industry; electronic payments; technical change; panel data